When Aesthetics, Surgery, and Psychology Meet: Aesthetic Nasal Proportions in Patients Having Rhinoplasty and Normal Adults - Mohsen Naraghi; Mohammad Atari; Hossein Asadollahi (The Surgery Journal, 2016)
Abstract The aesthetic nasal proportions have played a significant role in rhinoplasty practice. On the other hand, psychological variables also play a crucial role in rhinoplasty. It is of paramount importance for facial plastic surgeons to consider both sides to achieve a more satisfactory outcome. The present study aimed to compare aesthetic nasal proportions between primary rhinoplasty candidates and a demographically matched control group to determine whether patients having rhinoplasty have different aesthetic nasal proportions compared with healthy adults who are not interested in rhinoplasty. Sixty patients having rhinoplasty were selected consecutively from a surgical clinic. A control group (n = 60) with the same demographic characteristics was selected. Photographs were taken using a digital camera on a fixed zoom setting. All images were captured at a distance of 1.5 m. Frontal and right lateral views were used to compare nasolabial angle, nasofrontal angle, nasofacial angle, alar width, intercanthal distance, nasal length, and width-to-length ratio. Independent t tests were used for comparisons. Independent t tests verified that nasofrontal angle, nasal length, and width-to-length ratio were significantly different between the two groups (p < 0.01). Effect sizes ranged between 0.11 and 0.69. Aesthetic proportions were not significantly different in four factors. Nasolabial angle, nasofacial angle, alar width, and intercanthal distance were not different (p > 0.05). Four major aesthetic nasal proportions were statistically similar in a group of patients having rhinoplasty and a control group with no interest in rhinoplasty. Surprisingly, the patients having rhinoplasty showed a mean width-to-length ratio closer to aesthetic ideal. Therefore, applying for rhinoplasty may have strong psychological reasons (e.g., body dysmorphic symptoms) compared with realistic aesthetic appraisals.